Quality Management of Teacher Empowerment in Pekalongan Primary Islamic Schools - Nur Kholis; Fatah Syukur; Ade Ishs (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
A school's quality is heavily determined by the competence of its teachers. In terms of Islamic schools where building Islamic character in students serves as the main objective, the teachers play even a greater role. This article discusses concepts related to the empowerment of Islamic primary schools in Pekalongan. Promoting quality services to the community, the schools develop a strategy to empower their teachers. The research uses multiple case study whereby a variable-oriented approach is employed to develop a number of propositions upon which a cross-case analysis is constructed. This research article discusses theories related to human resource management, builds interconnection between the theories and the concept of teacher empowerment, and finally analyzes some profound findings upon which the schools are considered successful in empowering their teachers. It underscores the role of -amongst which- a teachers forum in improving the teaching and learning quality in the schools